Bibliometrics Analysis of English Teaching Method in Covid-19 Pandemic - Bungsudi Bungsudi; Fenny Thresia (Sociometry Journal of Social Science, Art and Humanity, 2021)
Covid-19 requires educators to innovate using the adaptive English teaching method. Various researchers have researched English teaching methods to solve the learning process in the Covid-19 pandemic. Therefore multiple studies need to be compiled into one discussion to produce information for the next researchers about future opportunities. This study conducts the Bibliometrics Analysis method to analyze the citation of research articles. The study population adopts article primer data of English teaching method in Covid-19 pandemic by searching through Google scholar with the key “English teaching method in Covid-19 pandemic” using Publish or Perish (PoP) software in December 2020. Based on the initial data search using the Publish or Perish (PoP) application, there were 989 articles. After screening the suitability of the topic, 63 articles were obtained, which became data to discuss. Data mapping results using the VOSViewer Software show the research trend is in the keyword that appears the most of sixty-three articles such as student, pandemic Covid, teacher, education, teaching, and EFL Teacher. Therefore, the next research potential uses other teaching media of the keyword summary presented by VOSViewer.